Pengaruh Profitability, Liquidity, dan Intensitas Modal terhadap Tax Avoidance pada Perusahaan Manufaktur yang terdaftar di BEI (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2025)
This study aims to determine how the influence of profitability, liquidity, capital intensity on tax avoidance on manufacturing companies listed on the IDX in the consumer non-cyclical sector companies. This research is quantitative research. The data used in this study are secondary data in the form of annual reports and sustainability reports of consumer non-cyclical sector companies listed on the Indonesia Stock Exchange for the period 2018-2023 which can be accessed through the Indonesia Stock Exchange website. The sampling method uses purposive sampling method. So that a total of 32 research samples were obtained from 126 companies with an observation period of 6 years, so that the total data in this study was 198 data. The data analysis technique used is descriptive statistical analysis. This study uses multiple linear regression analysis with the SPPS version 25 program. The results of this study indicate that the profitability, liquidity, and capital intensity variable have no effect on tax avoidance.
Keywords: Profitability; liquidity.; capital inntensity